Studies toward a World Catalog of Symphyta (Hymenoptera) - Blank, Stephan M.; Taeger, Andreas; Liston, Andrew D.; Smith, David R.; Rasnitsyn, Alexandr P.; Shinohara, Akihiko; Heidemaa, Mikk; Viitasaari, Matti (Zootaxa, 2009)
Taxonomic and nomenclatorial changes affecting Symphyta, resulting from work on a forthcoming world catalog, are proposed and explained. Dolerus zhelochovtsevi Heidemaa & Viitasaari, sp. nov. is described. One former subgenus and two former subspecies are now treated at genus or species level, respectively. Eighteen replacement names are given, 73 new synonymies and 78 new combinations are proposed, 3 synonymies are re-established, and 5 names are resurrected from synonymy. The precedence of 18 species names (nomina protecta) over their older synonyms (20 nomina oblita) is explained. Type species are designated for 8 genus-group names. One neotype and 17 lectotypes are designated. Five names described as varieties are assigned infrasubspecific rank. Twenty-five genus-group names associated with Arge, Corynis, Dolerus, Trichiosoma and Xyela are unavailable. Two genus-group names and 33 species-group names are considered as unplaced taxa. An identification key is presented for the West Palaearctic species of Profenusa MacGillivray, 1914. Notes on publication dates and authorships of names of certain taxa are also included.